The Effect of Slow Stroke Back Massage on Blood Pressure in Elderly Patients with Hypertension - Meidayanti, Gusti Ayu Made Diah Dwi; Candrawati, Sang Ayu Ketut; Lestari, Ni Kadek Yuni (Holistic Nursing and Health Science, 2023)
Hypertension is a non-communicable disease that is often diagnosed in the elderly population in the world. Some previous studies have also suggested that slow stroke back massage, is effective in lowering blood pressure in hypertensive patients. However, limited studies examine this therapy in elderly group. This study aims to determine the effect of slow stroke back massage on blood pressure in elderly hypertensive patients. This research method uses a type of quantitative research using quasi experimental design with two group pre-post-test nonequivalent control group design. The number of samples used were 44 respondents. Sampling using the simple random sampling technique was carried out 3 times a week with a duration of 10 minutes for 4 weeks. Inclusion criteria in this study were hypertension sufferers who were willing to be respondents, patients aged 45-74 years both male and female and patients taking hypertension medication. Exclusion criteria were patients who experienced burns, bruises, skin rashes, inflammation of the skin of the back, patients who had spinal fractures. The analysis used was univariate and bivariate using the parametric Paired Sample t-test and Independent t-test. The results obtained mean a decrease in systolic and diastolic blood pressure in the intervention group was 21.04 mmHg and 11.68 mmHg, p-value (0.000 <0.05). Meanwhile, the mean reduction in systolic and diastolic blood pressure in the control group was 3.00 mmHg with a p-value (0.071>0.05) and 2.04 mmHg with a p-value (0.081>0.05). The results of data analysis using the independent sample t-test obtained a p-value of 0.000 <0.05, which means that there is an effect of slow stroke back massage on blood pressure in hypertension sufferers. This study recommended slow stroke back massage as an alternative or supporting therapy in managing hypertension in elderly individuals because it does not cause side effects.